Padrões hidrometeorológicos e seus efeitos nas florações de cianobactérias no reservatório passo real, Rio Grande do Sul - Domingues, André Luis (2014)
Potentially toxic cyanobacterial blooms have been frequent in Brazilian lakes and reservoirs, causing economic issues as well as public health risks. In Rio Grande do Sul, a series of five reservoirs in the high course of the River Jacuí form a cascade system. One of the reservoirs, Passo Real, mainly accumulates water for hydroelectrical power generation and also regulates water flow to downstream reservoirs, amongst other uses. Blooms of cyanobacteria have been frequently recorded in this water body, possibly due to the long water residence time, associated to weather conditions and nutrient runoff from intense agricultural activities in the surrounding area. The study described herein aimed to: a) verify patterns of climatic, hydrological and limnological conditions, as well as their relationship with blooms of cyanobacteria; b) describe the yearly circulation regime, and thermal stratification of the water column; c) define the most favourable environmental conditions for the incidence of both dispersive and surface accumulative blooms, and also which species are adapted to each bloom type. 60 phytoplankton samples were taken from Passo Real reservoir between October 2009 and January 2013. Cyanobacteria species were identified and counted to estimate specific density and specific biovolume. Each bloom was assigned to a class: dispersive or surface accumulative. Measurements of solar radiation availability, solar shine, air temperature, rainfall, direction, and velocity of wind were taken, and also weather conditions for the sampling period were recorded. Hydrological (inflow, outflow, altitude, usable volume and residence time) and limnological (transparency, water temperature, pH, electric conductivity, total dissolved solids and chlorophyll-a) variables were also measured. The most influential variables favouring bloom formation were: intense rainfall (>20mm) up to ten days before sampling; air temperature mainly above 15ºC thirty days before sampling; low wind speed (<2m·s-1); high inflow caused by intense rainfall, coinciding with agricultural off season; long water residence time, 132 days on average on months with blooms; warmer temperatures and thermal stratification of the water between October and March. The reservoir was classified as warm monomictic, with only one complete vertical circulation in the winter and thermal stratification in the summer. Dispersive blooms were found when wind speed was above 7,9m·s-1, and surface accumulative blooms occurred when wind speed was below 5,5m·s-1. Species of the genus Dolichospermum were more adapted to produce dispersive blooms, mainly D. crassum and D. circinalis. On the other hand, species of Microcystis were better adapted to surface accumulative blooms, namely M. aeruginosa and M. panniformis, which were also indicator species for this type of bloom.